Human factors & safety culture: Challenges & opportunities for the port environment. (May 2020) - Corrigan, S.; Kay, A.; Ryan, M.; Brazil, B.; Ward, M.E.
Highlights: One of the very few empirical studies focusing on Human Factors and Safety Culture in the port environment. The application of a robust methodological approach that has been validated in applied industrial research. The application of the Safety Cultural Maturity Model. Provides a solid platform for future research in this 'under-researched' area. Provides high level recommendations for key steps ports need to consider on their journey towards a resilient safety culture. Abstract: The critical role of understanding Human Factors and the importance of Safety Culture in the maritime sector is becoming much more topical. While the key focus of much of the research in this sector has been on seagoing vessels, it is also important to recognise that ports and docks can be particularly dangerous and hazardous environments. The objective of this paper is to report on an exploratory research study assessing the safety culture and human factor awareness in a large European port environment. The research study adopted a multi-methods approach that included the completion of a Safety Culture Assessment Survey across a port environment (161 responses) and research interviews (11 in total) with a port authority company. The research concludes that there is an increasing awareness of human factors and a move towards a positive safety culture that facilitates an open and resilient approach to all safety practices. However much more focused research is required focusing on the specific complexities, constraints and shared processes of our port environments.